The Handbook of Salutogenesis 2022
DOI: 10.1007/978-3-030-79515-3_19
|View full text |Cite
|
Sign up to set email alerts
|

Older People, Sense of Coherence and Community

Abstract: In this chapter, the authors consider the meanings of the concepts of healthy ageing, ageing well, salutogenic ageing and reciprocity between the sense of coherence (SOC) and ageing processes. They discuss how the community can provide resources to strengthen older adults’ SOC, perceived well-being and quality of life. Quoting ‘It’s not how old we are; it’s how we are old’, the authors illuminate critical differences in understanding healthy ageing by professionals, researchers and older people themselves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 75 publications
(68 reference statements)
0
12
0
1
Order By: Relevance
“…The community with which the older adult maintains a sense of belonging and/or self-identification plays a crucial role in the proper development of GRRs. This has recently been confirmed by Koelen and Eriksson (2022), stating that the elders spend about 80% of their time in community and home. Accordingly, physical and social environment in which everyday life takes place must be a space conducive to active and healthy aging.…”
Section: The Salutogenic Approach To Population Aging: An Open Window...mentioning
confidence: 76%
“…The community with which the older adult maintains a sense of belonging and/or self-identification plays a crucial role in the proper development of GRRs. This has recently been confirmed by Koelen and Eriksson (2022), stating that the elders spend about 80% of their time in community and home. Accordingly, physical and social environment in which everyday life takes place must be a space conducive to active and healthy aging.…”
Section: The Salutogenic Approach To Population Aging: An Open Window...mentioning
confidence: 76%
“…The GRRs make it possible to access the SRRs, which in contrast ‘have situation-specific utility’ ( Mittelmark et al, 2017 , p. 71). Examples of SRRs are amenities and services like day care centres transport infrastructure, healthy food outlets and any other public accessible social places that can be considered health-promoting assets ( Koelen et al, 2017 ; Lake, 2018 ; Alidoust et al, 2019 ; Perez-Wilson et al, 2020 ). In this work, we can consider local high streets as GRRs because they are settings with wide-ranging utility, and their socio-spatial features as SRRs because these are specific to each local high street.…”
Section: Theoretical Foundations: Towards a Conceptual Framework For ...mentioning
confidence: 99%
“…The links between SOC, well-being and quality of life have been evidenced in studies that have looked at self-reported daily life experiences ( Eriksson and Lindström, 2006 , 2007 ). SOC has been used in relation to active travel and to access to green areas ( Koelen et al, 2017 ; Lillefjell et al, 2017 ), while age-friendly communities have identified the importance of everyday resources that can strengthen people’s SOC ( Koelen et al, 2017 ; Mittelmark et al, 2017 ).…”
Section: Theoretical Foundations: Towards a Conceptual Framework For ...mentioning
confidence: 99%
“…(7) Population aging is defined as a significant decline of fertility level in a certain group of people, that leads to infertility and mortality, and the increased proportion of elderly is calculated by comparing the number of the older population and the total population. (8) Indonesia has an aging population, since the proportion of elderly was 9.6% in 2019 or very close to 10%. The structure of the older population shows that the proportion of older people has increased over time.…”
Section: Introductionmentioning
confidence: 99%